Biocompatible lidocaine and prilocaine loaded-nanoemulsion system for enhanced percutaneous absorption: QbD-based optimisation, dermatokinetics and in vivo evaluation. (August 2015) - Negi, Poonam; Singh, Bhupinder; Sharma, Gajanand; Beg, Sarwar; Katare, Om Prakash
Abstract Barrier properties of the skin and physicochemical properties of the drugs are the main hiccups in delivering local anaesthetic molecules topically. The present work endeavours for systematic optimisation and evaluation of nanoemulsions (NEs) of local anaesthetic drugs, lidocaine and prilocaine, employing the systematic approach of Quality by Design. A 33 Box–Behnken design was employed for systematic optimisation of the factors obtained from screening studies employing Plackett–Burman design and risk assessment studies. The superior permeation rates, and higher concentrations of the drugs in skin layers from the optimised NE carriers, were achieved in permeation and dermatokinetic studies, when compared to marketed cream. Furthermore, rapid onset of action was demonstrated by the NE system in rabbit eye corneal reflex model and biocompatibility was confirmed from the absence of any marked skin change(s) in the normal skin histology. The developed NE systems demonstrated it as a promising carrier for topical delivery of lidocaine and prilocaine.